Maternal sensitivity and mother-infant attachment are associated with antibiotic uptake in infancy. (August 2022) - Fuertes, Marina; Gonçalves, Joana L; Faria, Anabela; Lopes-dos-Santos, Pedro; Conceição, Inês C; Dionisio, Francisco
Attachment security has been associated with health status and symptom reporting. In this longitudinal study, we investigated the association between antibiotics uptake by infants at 9-months and mother-infant attachment at 12-months. Logistic regression analyses indicated that lower maternal sensitivity was associated with increased odds of antibiotic uptake. Furthermore, 89.7% of insecure-ambivalent infants consumed antibiotics, which contrasted with 32.5% of avoidant infants and 21.5% of secure infants. This study suggests that maternal behavior and mother-infant attachment impact on antibiotic consumption, which is worrying because antibiotics may lead to several health problems later in life and antibiotic-resistance.